Comparação de elementos da Justiça de Transição no Brasil e no Chile e a atuação das Comissões da Verdade como instrumentos para a democracia (1961-2019) - Pastro, Tamara Claudia Coimbra (2020)
This work aims to compare the actions of the Truth Commissions and other mechanisms of Transitional Justice in Brazil and Chile. To do so, an interdisciplinary approach was used combining concepts and relationships from the areas of History, International Relations and the historical-comparative method. Thus, the period in which both states were in an exception regime was analysed, as well as the antecedents that triggered the military coups and their institutionalization and consolidation, allies with the systematic violations of Human Rights, used as state policy. Despite the different processes and experiences, points of similarities were found in redemocratization and three biases of analysis were elected: 1) the actions of truth commissions for the recognition of the victims of the State and for the settlement of the countries' accounts; 2) places of memory as their materialization and space of resistance; and 3) the trial of cases in the Inter- American Court of Human Rights (IACHR) to understand the crimes against humanity. Finally, we sought to understand how these experiences are still unfolding today by evaluating the capacity of States to guarantee the rights of victims and the functioning of democratic institutions.